The outer membrane proteins based seroprevalence strategy for Brucella ovis natural infection in sheep - Zhang, Tao; Wang, Yu; Li, Yin; Qi, Tingting; Yue, Zhirong; Cao, Lili; Zhou, Bo; Jiao, Huping (Frontiers in Cellular and Infection Microbiology, 2023)
Brucellosis diagnosis is largely dependent on tiger red plate agglutination test (RBPT). However, it is difficult to discriminate nature infected antibody positive and vaccinated antibody positive, nevertheless, the identification of specific Brucella species nature infection. Here, we analyzed the structure of main outer membrane proteins (OMPs), OMP 25 and OMP 31 from Brucella ovis (B. ovis) and Brucella melitensis (B. melitensis), which are the main agents of sheep brucellosis, and found the OMP 25 and OMP 31 could be used as the discriminated antigens for B.ovis and B. melitensis antibody. Then we expressed the OMP 25 from B. ovis (OMP25o) and OMP 31 from B. melitensis (OMP31m). They have equally efficiency in antibody detection of vaccinated sheep serum, consistent with the RBPT results. However, for the epidemiological investigations, we found some RBPT positive samples were negative by the OMP31m based serum antibody detection, but these samples gave positive results for the OMP25o. And we verificated these only OMP25o positive samples by B. ovis and B. melitensis specific primers based PCR detection, and all these samples were B. melitensis negative. However, four of six samples are B. ovis positive. These results showed that we could use the OMP25o and OMP31m to diagnose sheep brucellosis antibody, especially to discriminate the infection of the B. ovis. Currently, there is no approval for vaccines based on B. ovisin China, the B. ovis positive sample should be nature infected. There should be some B. ovis implicit transmission in Jilin province. Further epidemiological investigations should be conducted for the B. ovis nature infection.